Study on the mechanical properties and failure mechanism of a multi-lithologic layered rock mass - Bo Zeng; Guozhou Qiu; Haoyong Huang; Yintong Guo; Ersi Xu; Junchuan Gui; Junfeng Li (Heliyon)
The mechanical properties of multi-lithologic reservoir rock masses are complex, and the failure mechanism is not clear. This research belongs to the field of oil and gas exploration and development. Brazilian splitting, and digital image correlation (DIC) tests were performed to study the mechanical properties and failure mechanism of assemblages containing sandstone, shale, and limestone. In the Brazilian splitting test, the tensile strength of the rock mass first increased and then decreased with an increasing angle. As the interface angle increased, The morphology of the splits is also changing. In the DIC test, according to the deformation characteristics at different angles, the Brazilian splitting test process was summarized into three stages: interface deformation, elastoplastic, and failure, the interface has a great influence on the fracture propagation, and the fracture tends to expand along the interface. Interface characteristics were studied based on 3D scanning technology and fractal method, with an increase in the angle, the fractal dimension D showed first decreased, then increased, and further decreased, which was identical to the variation trend of the maximum load in the Brazilian splitting test and the maximum principal strain in the DIC test with the angle. This study provides reference for predicting fracture propagation trend in field hydraulic fracturing work.